The Importance of the School Functioning as an Organization and Teachers’ Work-Related Well-Being for Teachers’ Organizational Commitment - Bukšnytė-Marmienė, Loreta; Brandišauskienė, Agnė; Česnavičienė, Jūratė; Daugirdienė, Aušra (Psichologija, 2023)
The successful functioning of any organization depends on one of the most important factors – employees’ organizational commitment. As the modern education system strives to establish the school as an effective organization, it is important to investigate what psychological factors are associated with greater teachers’ organizational commitment. The aim of this study was to determine the implications of the school functioning as an organization and teachers’ wok related well-being for teachers’ organizational commitment. In this study participated 292 teachers. The factors of the school functioning were measured by the Organisational Diagnosis Questionnaire (Preziosi, 1980). Teachers’ work-related well-being was analysed as a continuum of job satisfaction and job insecurity. One of the subscales of the Michigan Organizational Assessment Questionnaire (Cammann et al., 1975) was used to measure job satisfaction. Job insecurity was measured with the Job Insecurity Scale (De Witte, 2000). Teachers’ organizational commitment was measured by the Organisational Commitment Scale (Balfour & Wechsler, 1996). The correlation analysis of the variables revealed that all the factors of the organizational functioning have statistically significant strong positive relationships. It was found that teachers’ work-related well-being is related to the school functioning factors. Teachers’ organizational commitment is related to both teachers’ work-related well-being and organizational functioning factors. A multivariate linear regression analysis found that 35.2 % of teachers’ organizational commitment was predicted by their job satisfaction, relationships, principals’ leadership and teachers’ perceived job insecurity.